ANALISIS PARTISIPASI PEMILIH PEMULA PADA PILKADA 2024 (PPS DI DESA KARANG TAPEN KECAMATAN CAKRANEGARA) - Muzilawati, Muzilawati; Maerani, Ahadiatun; Amanda, Baiq Citra Yuliantika; Dzulhakim, Danu; Andini, Firda; Munawwaroh, Wafiq Azizatun; Kurniawansyah, Edy (Universitas Sulawesi Tenggara, 2024)
This study aims to analyze the participation of first-time voters in the 2024 Regional Head Election (Pilkada) in Karang Tapen Village, Cakranegara District, Mataram City. The research employs a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, with the subjects being members of the Voting Committee (PPS) and first-time voters who participated in the polling station. The findings indicate that the participation rate of first-time voters in the 2024 Pilkada is quite significant, with nearly half of the voters in the 2005-2007 age group present at the polling stations. Factors supporting the participation of first-time voters include the support from family, friends, and social environment, as well as the motivation and awareness of voters regarding the importance of their voting rights. On the other hand, the hindering factors found include low levels of political education and understanding of voting rights, as well as limited knowledge of the candidates. These findings provide valuable insights to increase first-time voter participation in the future and suggest the need for enhanced political socialization and voter education to strengthen local democracy in Karang Tapen Village.